Classroom Assessment Practices and Student Goal Orientations in Mathematics Classes - Hülya Yıldızlı (Anı Publishing, 2020)
The present study aimed to explore classroom assessment practices (7th grade) in mathematics course and how these practices are perceived by students who had different goal orientations. In addition, the study also investigated how other classroom practices (i.e. comparisons, competition, and learning experiences), which allowed for a deeper description of classroom assessment practices, were perceived by students who had different goal orientations. In line with this aim, a mathematics teacher and one of his seventh grade mathematics classes were observed for a period of eight weeks. The study followed a mixed method methodology. The first part of the study was quantitative and aimed to collect and analyse quantitative data from students to identify their goal orientations. The qualitative part included two steps which focused on; a) teachers and b) students. The teacher dimension focused on the observation of teachers' classroom assessment practices which were related to other classroom practices that could be associated with students' goal orientations. The student dimension focused on the observation of three students' behaviours during teaching/learning processes. Those students were interviewed following observations. According to the results, classroom assessment practices and other classroom practices which could be associated with students' goal orientations are perceived differently based on students' goal orientations.